The role of optical CDMA in access networks. - Stok, A. (IEEE Communications magazine)
We investigate the possible role of optical CDMA (O-CDMA) in future access networks. We begin with a short review of the O-CDMA technique for those unfamiliar with the technology. Next, we investigate in detail those characteristics of O-CDMA that make it an attractive technology for application in metro access networks: fairness, flexibility, simplified network control and management, service differentiation, and increased security. Although O-CDMA has many favorable attributes, it also has several actual or perceived drawbacks. We discuss the technical, economic, and perception barriers that may have limited the widescale deployment of O-CDMA access networks. We try to determine which of these drawbacks may be surmountable in the near future and which may be true "showstoppers"